South Greenland Peregrine Falcon population monitoring data (1981-2021) - Falk, Knud; Møller, Søren (Zenodo, 2021)
The Peregrine Falcon ( Falco peregrinus tundrius ) population in South Greenland has been monitored annually 1981-2021 (except 1993, 2004 and 2020). At visits to known breeding sites we recorded presence/absence of territorial falcons as well as their breeding outputs (number of eggs and/or young). The file named S_Greenland_Peregrine_monitoring_data-1981-2021.csv contains the raw data from 835 site checks (sometimes several per site per year). The file named S_Greenland_Summary_occupancy_and_productivity-1981-2021.csv contains a summary of the raw data, providing annual estimates of occupancy, productivity and average brood size (young/ successful nest). The respective ReadMe files specify the contents. : {"references": ["K. Falk, S. M\u00f8ller, W.A. Burnham. The Peregrine Falcon Falco Peregrinus in South Greenland: Nesting requirements, phenology and prey selection. Dansk Orn.Foren.Tidsskr. 1986, 80, 113-120.", "K. Falk, S. M\u00f8ller. Status of the Peregrine Falcon in South Greenland: Population Density and Reproduction. In: Cade, T.J., Enderson, J.H., Thelander, C.G., White, C.M. (eds.) 1988. Peregrine Falcon Populations: Their Management and Recovery. Proc. 1985 Peregrine Conf., Sacramento, The Peregrine Fund, Boise, Idaho."]}